Democracy in Engineering Organisations. A Case Study of Kenya. - Ndolo, Antony (Open Science Journal, 2020)
In December 2019, the world was engulfed in coronavirus/COVID19 pandemic that spread like wildfire after emerging from Wuhan City, China. Naturally, this disrupted world's order and how organizations, including workplaces, are managed. In this short communication, we present what and how the Institution of Engineers of Kenya conducted their election campaigns and the election itself. The elections were held electronically. Number of voters' turnout shows some discrepancies as the total votes for the presidential post do not match that of the ordinary council member positions. It is therefore important to improve on transparency at the institution. We recomend that election should be handled by independent scrutineers. Any sitting council should not directly handle any election material. This will enhance accountability and service delivery to members.